Secondary school students' attitude and its effects on mathematics achievement / Aini Shuhaimah Selamat, Zarith Sofiah Othman and Siti Salwana Mamat - Selamat, Aini Shuhaimah; Othman, Zarith Sofiah; Mamat, Siti Salwana (Universiti Teknologi MARA, 2025)
This study examines students' attitudes and motivation toward learning mathematics. The purpose of the study is to determine the relationship between the variables of students' attitudes toward mathematics and their motivation to learn mathematics. The study also addresses the question of how non-intelligence variables affect student achievement. To answer the research questions, a questionnaire was administered to 150 grade 4 students who were surveyed. From the results, the relationship between these two variables is shown to be significant. However, the variables did not seem to affect the students' performance. It appeared that although the students had a positive attitude towards the subject and were highly motivated to learn mathematics, their performance in the exam was still poor. In conclusion, students' attitudes and motivation are variables that are closely related but may have no influence on students' performance in the subject. Further research on this topic can include elements that might be related to students' academic progress.